(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The level of productivity of crops depends upon the energy input during various farming operations. There is a direct relationship between energy use and agricultural production. Energy shortage and cost escalations will impede the growth of agriculture and its impact will be severe on crop production in the short-run. In this study, efficient management of scarce energy resources can play an important role in maintaining the growth in agriculture. This calls for energy conservation with a view to minimize energy use without affecting the crop production. To analysis the data on energy use pattern in the study area statistical tools such as multiple regression, chow’s test, input output analysis, Marginal value productivity (MVP) and factor analysis are used. This study concluded from the analysis that the largest share in the production of cotton was recorded by the bullock energy and the least share went to mechanical energy. It is understood that there is a need to improve cotton cultivation technology in order to increase the efficiency of energy inputs, used in the study area. Further, there is a scope for increasing the use of energy inputs so as to earn the maximum returns, Energy use efficiency can also be improved by practicing good husbandry, as there is scope for increasing yield through the use of higher inputs efficiently. There is a direct relationship between the energy use and agricultural production of cotton.